Hubungan prematuritas dengan kejadian asfiksia neonatorum - Pika Ardiana; Wafi Nur Muslihatun (Poltekkes Kemenkes Yogyakarta, 2016)
Asphyxia neonatorum contributes as much as 23% of 4 million neonates and fetus stillbirth 26% of 3.3 millionstillbirths annually. It is estimated that 1 million of children surviving from asphyxia have long term morbiditysuch as cerebral palsy, mental retardation and learning disorder. The prevalence of asphyxia at RSUDWonosari in 2012 reached 428 cases (32.64%), whereas premature birth increased from 51 cases (3.80%) to98 cases (7.47%). The aim of this study to find out correlation between prematurity and first minute asphyxianeonatorum in the newborn at RSUD Wonosari in 2012. The method of this study used cross sectional design.Location of the study was RSUD Wonosari. Subjects were the newborn in 2012. Variables of the study wereprematurity as the independent variable and first minute asphyxia neonatorum as the dependent variable. Datawere obtained from secondary data of medical records. Sampling used purposive method. Analysis ofcorrelation between the two variables used Chi-square. Stratified analysis used Mantel-Haenszel. Result: theresult of Chi-square showed significance 0.000 (p<0.01) at confidence interval 99%. There was significantcorrelation between prematurity and first minute asphyxia neonatorum. The result of stratified test showedprevalence ratio as much as 2.39. Conclusion: there was correlation between prematurity and first minuteApgar score in the newborn. Premature birth increased risk 2.39 times for the newborn with asphyxianeonatorum than baby wasnot premature.